Peran Kepemimpinan Kepala Sekolah dalam Menciptakan Iklim Kerja Kondusif bagi Guru di SDN 2 Sendangmulyo - Tumeko, Dwi Satrio Bagus; Rasiman, Rasiman; Supandi, Supandi (Cetta: Jurnal Ilmu Pendidikan, 2025)
A conducive work climate is a key factor in creating a productive school environment and enhancing teacher performance. A positive work environment not only boosts teacher motivation and enthusiasm but also impacts the quality of learning. This study aims to describe the role of school principal leadership in creating a conducive work climate to improve teacher performance at SDN 2 Sendangmulyo. This research employed a descriptive qualitative approach with data collection techniques including in-depth interviews, participatory observation, and documentation of leadership practices and the work atmosphere among teachers. The findings indicate that the principal plays a strategic role through communicative, inclusive, and transformative leadership. The principal fosters open and two-way communication, creates a harmonious and supportive work environment, and promotes a collaborative culture among teachers. Supervision is carried out regularly with a coaching-oriented approach, accompanied by constructive feedback. The principal also acknowledges and appreciates teachers’ dedication through both formal and informal recognition. Furthermore, the principal provides adequate physical facilities, access to learning resources, and opportunities for professional development through training and seminars. The conclusion of this study highlights that the principal's leadership strategies play a significant role in shaping a work climate that supports sustainable improvement in teacher performance. Humanistic, communicative, and supportive leadership is key to building a school that emphasizes quality and professionalism.